PROBLEMS OF HYDROLOGICAL ZONING OF THE TERRITORY OF BELARUS (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
Approaches to the need to adjust the hydrological zoning of the territory of Belarus are analyzed. The methods and history of the development of hydrological zoning of the territory of the USSR and Belarus, the patterns of spatial distribution and runoff variability, and the scientific substantiation of runoff in different regions are considered. A variant of hydrological zoning based on basin, landscape and hydrological principles is proposed.
Keywords: hydrological zoning; network optimization; history; runoff analysis; series; statistics; runoff; runoff fluctuations; spatial differences; variations